Full Poincaré polarimetry for enhanced microscopic sensing - He, C; Booth, MJ (Optica Publishing Group, 2021)
A new polarisation sensing paradigm circumvents the limitations of traditional approaches. We use a GRIN optic for universal polarisation mapping. Mean errors <1% for each Stokes vector component lead to more sensitive polarimetric microscopy.